Sampling and analysis of iron, steel and other ferrous metals. Methods of analysis. Determination of silicon. Steel and cast iron: spectrophotometric method for silicon contents from 0.01% (m/m) to 0.05% (m/m) Part 3.26.4, (31st December 1989) - British Standards Institution,
No abstract available